Principals’ Effective Task Performance: A Tool for Proper Education Delivery in Nigerian Secondary Schools - Hamza Usman (Journal of Islamic Economics and Social Science (JIESS), 2020)
Secondary schools have nowadays become more complex than ever before. This is because of the ever growing number of students and population of the staff. The school principal should possess certain qualities that would enable him to face the administrative tasks efficiently and effectively in order to achieve the school goals and objectives. This paper therefore, reviewed the Principals’ Effective Task Performance as tool for proper Education Delivery in Nigerian Secondary Schools. The tasks of the principal in meeting these challenges were examined as the chief executive, relating to system and human relation theories. Qualities of an ideal school principal were highlighted, emphasizing on transformational leadership qualities. Tasks of the principal were also highlighted; instructional supervision, and motivation of staff. The paper concluded that, leadership qualities are strong determinants of principals’ tasks performance effectiveness in proper delivery of secondary schools education in Nigeria. Principals’ leadership qualities influence effective school administration. Finally recommended that, the principals should be well prepared; knowledgeable, professionally and administratively competent for the challenges involved in the mantle of leadership. Government should from time to time be organising conferences and workshops for the principals. Sponsorship is a mark of encouragement.